Physical quality of maize grain harvested and stored by smallholder farmers in the Northern highlands of Tanzania: effects of harvesting and pre-storage handling practices in two marginally contrasting agro-locations - Mutungi, C.; Muthoni, F.; Bekunda, Mateete A.; Gaspar, A.; Kabula, E.; Abass, A. (Elsevier, 2019)
On-farm trials were conducted to investigate the effects of maize harvesting and handling practices of smallholder farmers on the quality of the produce before, and during storage in two contrasting agro-locations. Farmers harvested and prepared the crop according to local practices, and stored it in ordinary woven polypropylene bags for 30 weeks. Grain moisture, insect populations, insect-damage, moldy/diseased/discolored grain, rodent-damage, shriveled grain, broken grains, non-consumable grains, impurities, and overall losses were monitored. Moisture of the pre-stored grain ranged between 11.0 and 23.7% while the overall physical damage was 16.9 ± 6.2%. Late harvesting increased moldy/diseased/discolored grain two-fold while de-husking and drying practices increased the levels in early-harvested grain by factor of 2–3. Insect populations were >10 times higher in the cooler agro-location, and handling practices increased them by factor of 2–10. The interaction of agro-location, harvesting time and drying influenced the amount of grain that was unfit for human consumption. Pre-storage losses of 3.6–11.2% were determined, mainly as grade-outs. With storage, the quality of early-and late-harvested maize did not differ. However, the majority of examined parameters were distinct by agro-location. Moreover, secondary pests and the levels of shriveled and broken grain levels were also distinct by drying method, while moldy/diseased/discolored grain, non-consumable grain, and overall losses were distinct depending on whether the harvested cobs were de-husked or not de-husked before drying. The high levels of grade-outs at the pre-storage stage suggest that sorting should be emphasized for quality improvement at the farm gate not only for the market but also household nutrition. Cultivation of varieties with superior maturing and post-harvest traits would lower the sorting losses. Agro-location and farmer practices influenced grain quality and magnitude of losses during storage. These findings should inform choice of intervention steps right from the pre-storage stage.